PENGARUH MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI (Studi Kasus Pada Dinas Tenaga Kerja Dan Transmigrasi Kabupaten Sambas) - Rosita, Neny; wahab (Cross-Border Journal of Business Management, 2024)
The success of an organization is influenced by many factors, one of which is employee performance. Meanwhile, employee performance is influenced by motivation and work environment. If motivation and work environment experience problems, it will affect employee performance. This study aims to test and determine the effect of motivation and work environment partially and simultaneously on employee performance at the Sambas Regency Manpower and Transmigration Office. The type of data in this study is quantitative with descriptive data analysis using primary data and secondary data obtained from the Sambas Regency Manpower and Transmigration Office. The number of samples in this study were 51 respondents using nonprobability sampling technique with saturated sampling method. The sample taken from the respondent is the answer to the questionnaire from the respondent. The data analysis method used is instrument test, classical assumption test, hypothesis testing using multiple linear regression test, t test, F test and coefficient of determination. Based on the results of multiple linear regression analysis with the help of the SPSS version 22 program, it is known that work motivation variables have a positive effect on employee performance with a significant value of 0.000 < 0.05 and a tcount t value of 5.145> t table 1.677. work environment variables have a positive effect on employee performance with a significant value of 0.000 < 0.05 and a tcount t value of 5.180> t table 1.677. Simultaneously, motivation and work environment variables have a significant effect on employee performance with a significant value of 0.000 <0.05. The coefficient of determination in this study is 66.3% and the remaining 33.7% is influenced by other variables not used in this study. Keywords: Work Motivation, Work Environment, Employee Performance